The long-run relationship between inflation and real stock prices: empirical evidence from South Africa - Arjoon, Riona; Botes, Mariëtte; Chesang, Laban K.; Gupta, Rangan (Journal of Business Economics and Management, 2012)
The existing literature on the theoretical relationship between the rate of inflation and real stock prices in an economy has shown varied predictions about the long run effects of inflation on real stock prices. In this paper, we present some time series evidence on this issue using South African data, by applying the structural bivariate vector autoregressive (VAR) methodology proposed by King and Watson (1997). Our empirical results provide considerable support of the view that, in the long run real stock prices are invariant to permanent changes in the rate of inflation. The impulse responses reveal a positive real stock price response to a permanent inflation shock in the long run, indicating that any deviations in short run real stock prices will be corrected towards the long run value. It is therefore concluded that inflation does not lower the real value of stocks in South Africa, at least in the long run.